Hi there!
FACT :
The method of solving "by substitution" works by solving one of the equations for one of the variables, and then plugging this back into the other equation, "substituing" for the variable and solving for the other.
STEPS TO ANSWER :
x + y = 3
x = 6 - 4y
1.
Replace the "x" in the first equation with : 6 - 4y
And then solve the equation by isolating "y".
6 - 4y + y = 3
Subtract 6 from each side of the equation → 3 - 6 = -3
-4y + y = -3
Add similar terms together → -4y + y = -3y
-3y = -3
Divide each side of the equation by -3 → -3 ÷ -3 = 1
y = 1
2.
Now that you have the value of "y", it's time to plug its value back into the other equation and solve this equation for "x" :
x = 6 - 4y
y = 1
Replace the "y" in the first equation by : 1
And then solve the equation by isolating "x".
x = 6 - 4(1)
→ -4 × 1 = -4
x = 6 - 4
→ 6 - 4 = 2
x = 2
Answer : The solution pair of coordinates is : (2 ; 1).
There you go! I really hope this helped, if there's anything just let me know! :)